The goblin spider genus Ischnothyreus (Araneae, Oonopidae) in Java and Sumatra - Richard, Miguel; Graber, Werner; Kropf, Christian (Zootaxa, 2016)
The genus Ischnothyreus Simon, 1893 from Java and Sumatra is revised with the description of seven new species from Java (I. baltenspergerae sp. nov., I. bauri sp. nov., I. gigeri sp. nov., I. ligulatus sp. nov., I. nentwigorum sp. nov., I. sigridae sp. nov., I. ujungkulon sp. nov) and eight from Sumatra (I. ascifer sp. nov., I. concavus sp. nov., I. habeggeri sp. nov., I. haymozi sp. nov., I. lucidus sp. nov., I. marggii sp. nov., I. microphthalmus sp. nov., I. obscurus sp. nov.). Furthermore the male of I. serpentinum Saaristo, 2001 is described for the first time and the female redescribed in detail. Special morphological features of Ischnothyreus males and females are described and discussed, such as peculiar trochanter projections, partially fused pedipalp segments, processes on the cheliceral fang base in males and external and internal genitalic structures in females. This work is part of the Planetary Biodiversity Inventory (PBI) of goblin spiders (http://research.amnh.org/oonopidae/).